2021
DOI: 10.1016/j.celrep.2021.109496
|View full text |Cite
|
Sign up to set email alerts
|

Slow AMPA receptors in hippocampal principal cells

Abstract: Highlights d Two-thirds of principal cells in the hippocampal CA1 region express slow AMPA receptors d Slow AMPA receptors show reduced desensitization and stay active for up to half a second d Increased charge transfer allows single stimulations to trigger action potentials d Postsynaptic short-term potentiation has implications for computation and cognition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Moreover, the slower decay kinetics of AMPARs and the increase in charge transfer may indicate a change in postsynaptic AMPAR subunit composition ( Chater and Goda, 2014 ) where more slow calcium-impermeable GluA2-containing AMPARs with longer decay and charge transfer are inserted at glutamatergic synapses by mTBI. In fact, recent evidence suggest that almost half of glutamatergic synapses onto CA1 pyramidal neurons express slow AMPARs that exhibit reduced desensitization ( Pampaloni et al, 2021 ). Consistently, in our recent study ( Selvaraj et al, 2021 ), we observed changes in AMPAR subunit composition following mTBI at 8 and 32 days post-injury using Western blot analysis of whole hippocampal tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the slower decay kinetics of AMPARs and the increase in charge transfer may indicate a change in postsynaptic AMPAR subunit composition ( Chater and Goda, 2014 ) where more slow calcium-impermeable GluA2-containing AMPARs with longer decay and charge transfer are inserted at glutamatergic synapses by mTBI. In fact, recent evidence suggest that almost half of glutamatergic synapses onto CA1 pyramidal neurons express slow AMPARs that exhibit reduced desensitization ( Pampaloni et al, 2021 ). Consistently, in our recent study ( Selvaraj et al, 2021 ), we observed changes in AMPAR subunit composition following mTBI at 8 and 32 days post-injury using Western blot analysis of whole hippocampal tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Properties of slow AMPA receptors denoted with an asterisk are from Pampaloni et al . (2021). A high affinity for glutamate is inferred from the slow decay.…”
Section: Evidence For Slow Ampa Receptors In Brainmentioning
confidence: 99%
“… A , uncaging 4‐Methoxy‐7‐nitroindolinyl‐glutamate (MNI‐glutamate) at 10 Hz reveals a mosaic distribution of slow, accumulating pedestal responses (marked with magenta box in each panel) in CA1 pyramidal cells in the hippocampus (Pampaloni et al . 2021). B , heteromeric AMPA receptors in complex with γ‐8 allow slow responses resistant to inhibition by NBQX.…”
Section: Evidence For Slow Ampa Receptors In Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…To distinguish between these possibilities, we conducted patch clamp recordings of organotypic slice cultures, in which AMPAR surface levels can be monitored upon glutamate uncaging at dendrites ( Fig. 3D ) ( 36 ). As surface-localized GluA1-homomeric CP-AMPARs are sensitive to a block of their outward currents at positive holding potentials by intracellular polyamines leading to pronounced inward rectification ( 37 ), they can be readily distinguished from GluA2-containing CI-AMPARs.…”
Section: Introductionmentioning
confidence: 99%